2016
DOI: 10.1039/c6ra07626b
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide: strategies for synthesis, reduction and frontier applications

Abstract: Till now, several innovative methods have been developed for the synthesis of graphene materials including mechanical exfoliation, epitaxial growth by chemical vapor deposition, chemical reduction of graphite oxide, liquid-phase exfoliation, arc discharge of graphite, in situ electron beam irradiation, epitaxial growth on SiC, thermal fusion, laser reduction of polymers sheets and unzipping of carbon nanotubes etc. Generally large scale graphene nanosheets are reliably synthesized utilising other forms of grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
219
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(225 citation statements)
references
References 266 publications
2
219
0
4
Order By: Relevance
“…Thus, considerable efforts have been made to enhance the SC performance by creating composites of TMOs and carbon materials, such as TMOs/graphene and TMOs/ carbon nanofibers (CFs) [154][155][156][157][158][159][160][161][162][163][164][165][166][167]. The synthesized multi-component composites can maximize the benefits from all components [154][155][156][157][158][159][160][161][162][163][164][165][166][167][168][169].…”
Section: Composites Of Carbon Materials and Tmosmentioning
confidence: 99%
“…Thus, considerable efforts have been made to enhance the SC performance by creating composites of TMOs and carbon materials, such as TMOs/graphene and TMOs/ carbon nanofibers (CFs) [154][155][156][157][158][159][160][161][162][163][164][165][166][167]. The synthesized multi-component composites can maximize the benefits from all components [154][155][156][157][158][159][160][161][162][163][164][165][166][167][168][169].…”
Section: Composites Of Carbon Materials and Tmosmentioning
confidence: 99%
“…[51,52] Utilization of high energy photoirradiance was also shown to be an effective and energy-efficient way to repair defective RGO structures. [53,54] It has been demonstrated that through significantly lowered structural defects, such highly reduced GO (HRGO) products helped bring about significantly enhanced functional properties for chemical energy storage devices such as metal-ion batteries and supercapacitors (SC), when good crystallinity and associated high electric/ thermal conductivity are essential, as is summarized in Table 1. [55][56][57][58][59] In this work, we focus on reviewing recent advances for the production of HRGO and their applications to chemical energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, reduced graphene oxide (rGO) can be achieved by simple and low cost synthesis methods, and shows properties similar to graphene sheets. Hence, there are numerous works which have utilized rGO sheets, benefiting from graphene-like properties [10,11].…”
Section: Introductionmentioning
confidence: 99%